COMPARATIVE PUBLIC ADMINISTRATION: THE ESSENTIAL READINGS - ERIC E. OTENYO, NANCY S. LIND (Elsevier, 2006)
There was a time, not long ago, when the study of comparative public administration had nearly slipped off the academic agenda. Interest in the administration of colonies by major powers evaporated, and concern about development administration slipped. A handful of scholars, led by many of the luminaries who have contributed to this book, kept the field alive. They rightly remained convinced of its importance, but many other experts pushed it aside. That changed with the rise of the ‘‘new public management’’ in the late 1970s and early 1980s. The scope of comparative public administration broadened, from a focus on knowledge transfer from developed to developing nations to embrace efforts to help develop nations transform themselves. New Zealand’s efforts to shrink the size of its government and radically transform its administrative structure caught the attention of the world. As the movement spread, to the United Kingdom, to other nations with a Westminster style of government, and then to other nations as well, recurring themes emerged. Just what is this ‘‘new public management’’? Was it a fad, or was there something more enduring at work? And from the experiences of the vast global experimentation in government reform, could we learn deeper lessons about governance? Comparative public administration reemerged, attracting a new generation of scholars and focusing on an even richer collection of issues. The classic issues – just what is comparative public administration, and how can we sensibly make comparisons? – became the foundation for a new set of puzzles – what is the relationship between administration and the state, and how can we transform public administration to improve public governance? Debates in the field became far livelier and drew in a far broader array of participants. Students of public administration came to realize that any study of a single nation’s administrative apparatus had to include a comparative dimension. That analysis provides the bright light that identified what was truly interesting and distinctive about the system, and how it might be changed. Students of comparative politics came to realize, even more fundamentally, just how important the administrative system was to the way governments operated.